LANGUAGE USE BETWEEN MEN AND WOMEN - Tri Rina Budiwati (Celt: A Journal of Culture, English Language Teaching & Literature, 2004)
Sex differences bring a consequence of difference in language use between men and women. From the long process of socio-cultural legitimization in gender, the difference is assumed predestine that gives consequence of inequality of sex treatment in language. In short, sex and gender differences pervade all aspects of language. English use between men and women manifests in phonology, morphology and vocabulary, intonation patterns, and conversational styles.